2013
DOI: 10.1200/jco.2013.31.15_suppl.4086
|View full text |Cite
|
Sign up to set email alerts
|

FOLFIRI plus sunitinib versus FOLFIRI alone in advanced chemorefractory esophagogastric cancer patients: A randomized placebo-controlled multicentric AIO phase II trial.

Abstract: 4086 Background: Sunitinib is an receptor tyrosine kinase (RTK) inhibitor of VEGFR1-3, PDGFR-α-β, and other RTK. After we established Sunitinib (Sun) alone associated with limited response rate (RR) and good tolerability in refractory advanced esophagogastric cancer patients (Moehler et al. EUR J Cancer. 2011, 47: 1511), this double-blinded placebo-controlled phase II evaluated safety and efficacy of SUN as add-on in second-line or third-line FOLFIRI (ClinicalTrials.gov NCT01020630). Methods: Patients with fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The sample size in the included trials varied from 91 to 774, the median age of the enrolled patients ranged from 52 to 65 years. Of these, two studies [ 25 , 26 ] enrolled patients who were treated with anti-VEGF-based drugs, five studies [ 9 11 , 13 , 27 ] enrolled patients who were treated with anti-VEGFR-2 agents, and three trials [ 18 , 23 , 24 ] enrolled patients who were treated with inhibitors of multiple tyrosine kinases (one of the targets is VEGFR-2). Four trials [ 18 , 25 – 27 ] were conducted in the first-line setting and the other six trials [ 9 11 , 13 , 23 , 24 ] in the pretreatment setting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size in the included trials varied from 91 to 774, the median age of the enrolled patients ranged from 52 to 65 years. Of these, two studies [ 25 , 26 ] enrolled patients who were treated with anti-VEGF-based drugs, five studies [ 9 11 , 13 , 27 ] enrolled patients who were treated with anti-VEGFR-2 agents, and three trials [ 18 , 23 , 24 ] enrolled patients who were treated with inhibitors of multiple tyrosine kinases (one of the targets is VEGFR-2). Four trials [ 18 , 25 – 27 ] were conducted in the first-line setting and the other six trials [ 9 11 , 13 , 23 , 24 ] in the pretreatment setting.…”
Section: Resultsmentioning
confidence: 99%
“…All included studies [ 9 11 , 13 , 18 , 23 – 27 ] reported OS, and nine trials [ 9 11 , 13 , 18 , 24 – 27 ] reported PFS. One study [ 23 ] reported time to progression (TTP).…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that PFS at 24 weeks was 25% (90% CI: 12–42%), which was not improved from historical control ( Schmitt et al , 2012 ). In addition, a randomised placebo-controlled phase II study of FOLFIRI with or without sunitinib in 91 patients with advanced GE cancers showed that median PFS was similar in the sunitinib vs placebo arm (3.6 vs 3.3 months, respectively, HR 1.11, 95% CI: 0.70–1.74, P =0.66; Moehler et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of treatment with the FOLFIRI (irinotecan, leucovorin, and fluorouracil) regimen plus sunitinib versus FOLFIRI alone in patients with advanced chemotherapy-refractory esophagogastric cancer, showed that sunitinib added to FOLFIRI increased hematotoxicity and did not improve ORR or PFS in chemotherapy-resistant patients. 59 …”
Section: Sunitinib In Solid Cancersmentioning
confidence: 99%